Implementation COBIT 5 Framework for Measuring E-Government Maturity at Ministry of Law and Human Rights - Ayu Bintang Nurrachma Gunawan; Dana Indra Sensuse (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The implementation of E-Government has been widely carried out by the current government to realized good governance to serve the citizen nowadays. The Ministry of Law and Human Rights or better known as the Kemenkumham in Indonesia, has implemented E-Government in various business processes (services). Still, in its implementation, E-government's application has not fully been able to maximize government services in organizations. The absence of an evaluation of the results of the application of E-Government is also an obstacle for management in making decisions in the planning, control, monitoring, and implementation of E-Government at the Kemenkumham. Therefore, we need a general maturity framework capable of guiding E-Government development and overcoming problems that arise. This study aims to measure the maturity level of e-government implementation by evaluating the E-Government system at the Kemenkumham. Measurement of maturity level is carried out by using the COBIT framework as an e-government maturity model involving 3 main domains, 6 aspects and 34 indicators in e-government on the capability of technical fungctions. The research method used was a survey method within the Kemenkumham. By these studies that the evaluation results would get recommendations for improvements in implementing E-Government for the next period.